Prevalence, Lifestyle Factors and Health Effects of Dysmenorrhea Among Female Students at Private Universities in Osun State, Nigeria (Fountain Journal of Natural and Applied Sciences, 2022)
Dysmenorrhea is a major gynaecological issue among female students in Nigeria. This study investigated the Prevalence, lifestyle factors, and health effects of dysmenorrhea among female students at private Universities in Osun State, Nigeria. The cross-sectional descriptive study used a multistage sampling procedure to select participants randomly across selected private Universities in Osun State. A validated-structured questionnaire was used to gather data from participants. Data analysis using descriptive and inferential statistics at p
Keywords: Prevalence, Lifestyle, Dysmenorrhea, Female Students